Discriminant Analysis and Optimization Applied to Vibration Signals for the Quality Control of Rotary Compressors in the Production Line - REIS, Déborah Aparecida Souza dos; VANZO, Fernanda do Carmo Silvério; REIS, Jorge von Atzingen dos; DUARTE, Marcus Antonio Viana (Archives of Acoustics, 2019)
In this paper, the applications of the multivariate data analysis and optimization on vibration signals from compressors have been tested on the assembly line to identify nonconforming products. The multivariate analysis has wide applicability in the optimization of weather forecasting, agricultural experiments, or, as in this case study, in quality control. The techniques of discriminant analysis and linear program were used to solve the problem. The acceleration and velocity signals used in this work were measured in twenty-five rotating compressors, of which eleven were classified as good baseline compressors and fourteen with manufacturing defects by the specialists in the final acoustic test of the production line. The results obtained with the discriminant analysis separated the conforming and nonconforming groups with a significance level of 0.01, which validated the proposed methodology.